Nano-Silica and Biopolymer Hybrid Composites for Sustainable (Bio)Organic Sensing Applications - Jassim, Amar Yasser; Kadhum, Wesam R.; kianfar, Ehsan (Journal of Composites and Biodegradable Polymers, 2025)
In the chemical industry, the development of sustainable economic strategies for accessing products with high added value from substitutes and cheaper sources is now more of a challenge. Silica is one of the most frequently used chemicals and is often used in many industrial applications, such as in toothpaste as a cleaning agent, in the rubber industry, and as a reinforcing material. This essay summarizes alternative approaches for the synthesis of salt and hybrid geocide materials. So far, these phases have been synthesized from molecular silane precursors via water-splitting sol-gel chemistry or chlorinated silane incineration processes, and thus indirectly from quartz sand. However, quartz sand is a non-renewable resource, and the scarcity of actual sand is becoming increasingly problematic for various processes in the chemical industry. In fact, quartz sand is the second most common raw material in the world, and its availability has a major impact on many production processes. B. Healthcare or electronic devices. In the actual context of sand shortage, the drafting of silica-based materials is increasingly attracting interest from alternative sources. This summary article discusses the new possibilities for access to bio sourcing and material-based sources such as renewable starting materials, electrical and electronic equipment in waste equipment, or fluorosilicic acid, a by-product of the phosphate industry. Silica must be considered a valuable raw material, and it demonstrates that alternative production processes from renewable resources, as well as cyclical lifetime assessments and valuable recycling strategies for these materials should be considered in consideration of the creation of sustainable and periodic production processes. The exciting science of organic devices has brought about a completely new stage of feasible bio detecting innovation, which offers a prospective horizon for applications in therapeutic diagnostics and organic checking. This audit report provides a thorough analysis of the remarkable advancements in organic electronic devices and their potential for bio detection applications. The need for more accurate, more affordable, and more capable sensors was felt as a result of global scientific advancements, the development of electronic equipment, and the enormous changes that occurred over the last several decades. In order to be sensitive to minute amounts of gas, heat, or radiation, sensors with high affectability are used nowadays. It is necessary to disclose underused materials and devices in order to increase the affectability, capability, and accuracy of these sensors. Due to their small and nanoscale estimates, Nano sensors—sensors that are nanometers in size—have exceptionally high precision and responsiveness, allowing them to react without a doubt to the proximity of many gas particles. Compared to conventional sensors, Nano sensors are inherently more delicate and smaller.